The relationship between hearing and cognition during aging: dichotic listening as an assessment tool - Ivern, Ignasi; Valero, Jesús; Signo, Sara; Vila, Josep Mª; Català, Mercè; Talleda, Natàlia (Revista de Investigación en Logopedia, 2017)
The aim of this research was to examine the relationship between hearing and cognition in ageing by assessing the incorporation of the dichotic listening technique into the usual clinical protocol for the elderly. 80 subjects (40 men and 40 women) were selected, with ages ranging from 65 to 85 years, and organized in 4 groups depending on the presence or absence of Hearing Loss –HL- and Mild Cognitive Impairment –MCI-. After administering a dichotic listening test based on verbal stimuli (syllables with CW structure), a statistically significant Right Ear Advantage –REA- was found in all groups. However, there were no significant differences among the different groups despite results showing a lower lateralization index in the group of individuals with HL and MCI. In addition, dichotic listening tests shows as a simple and very suggestive technique for exploration of the state of the auditory pathway and also for possible cognitive impairment. But we must be very cautious when we provide information on its usefulness as a diagnostic tool.
Keywords: Aging; Dichotic Listening; Hearing Loss; Laterality Index; Mild Cognitive Impairment; Right Ear Advantage.